KEMAMPUAN BERPIKIR MAHASISWA CALON GURU DALAM PENGAJUAN SOAL MATEMATIKA TIPE POST SOLUTION POSING DITINJAU DARI GAYA BELAJAR - Mei, Agustina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This study aimed to describe the thought process student teachers in the filing of post-type math problem posing solution in terms of learning styles. Filing post about the type of solution posing as students to modify the conditions of interest or questions that have been completed to generate new problems. While the learning styles that students who have learning styles are visual, auditory and kinesthetic (V-A-K) This study used a qualitative approach and data collection techniques done with the learning styles test, test the submission of questions and interviews. This study used three students of University Mathematics Education FKIP Flores who have learning styles are visual, auditory and kinesthetic. The data analysis is done by step - step, namely the reduction of data, presenting data and draw conclusions. As for obtain valid research data, this study used triangulation of time. Subjects who have a visual learning style, can receive information by writing the note and asked on the matter and establish the mathematical model of any information contained on the matter. Subjects in processing information that could link the information given to the concept stored in memory that is the subject says the concept uses existing linear program and derivative material. In finding a way in solving strategies, subject to form models/equations to obtain a set tariff in order to gain the maximum profit. Subject to draw conclusions made about the same as the submission of test questions but changed the context of the information and asked different. Subjects who have auditory learning style, in receiving information by writing and calculating the net profits of each set price and subsequent counting using excel. Subject to process information that is subject may connect the information given to the concept stored in memory that is the subject says the concept uses existing linear program in calculating gains and losses.